IMPROVING DISTANCE LEARNING PROCESS IN ENGINEERING EDUCATION USING DESIGN OF EXPERIMENTS: RE-DESIGN OF AN ONLINE INDUSTRIAL ENGINEERING COURSE DURING AND BEYOND THE PANDEMIC COVID-19 - Goumairi, Ouissal; Aoula, Es-Saâdia; Ben Souda, Souad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Abstract: This study aims to improve the quality of the learning process in engineering education. The ‎COVID-19 ‎health crisis pushed the scientific community to review teaching practices and reconsider ‎their effectiveness. ‎Engineering education and learning were not an exception to that. This article ‎introduces a case study using the Design of Experiments method to improve ‎engineering education quality, especially ‎in the distance learning process. In this case study, we focused on ‎designing the process of distance ‎learning and its quality by working on the case of two industrial ‎engineering classes (2021 and 2022 ‎classes) in a Moroccan public engineering school. ‎The collaboration between the teacher and these two engineering students’ classes in their third year of ‎industrial engineering enabled us to identify factors influencing ‎learning ‎quality. Then, we determined the optimal ‎combinations of these factors for better quality by ‎analyzing the results of the experiments.‎ The Design of Experiments successfully implemented in ‎manufacturing can also be applied to ‎engineering education settings. The result of this study ‎would help teachers and decision-makers ‎understand the factors that influence the quality of ‎learning to improve the distance learning process.‎